2007
DOI: 10.1532/hsf98.20071136
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Modalities in Hypertrophic Obstructive Cardiomyopathy: Surgical Myectomy versus Percutaneous Septal Ablation

Abstract: The 2 approaches yielded similar results with regard to reducing the LVOT gradient. We conclude that SM is preferable to PSMA in cases with MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…Ralph-Edwards et al (9) reported a significantly higher post-procedure SAM in patients undergoing SA than those undergoing SM (OR: 4.8; 95% CI: 2.0 to 11.9). No significant differences in SAM occurrence were encountered in other studies (10,11,14).…”
Section: Resultscontrasting
confidence: 53%
See 4 more Smart Citations
“…Ralph-Edwards et al (9) reported a significantly higher post-procedure SAM in patients undergoing SA than those undergoing SM (OR: 4.8; 95% CI: 2.0 to 11.9). No significant differences in SAM occurrence were encountered in other studies (10,11,14).…”
Section: Resultscontrasting
confidence: 53%
“…Two studies (13,15) reported a significantly higher LBBB after myectomy, compared with after ablation. On the contrary, Vural et al (11) reported higher LBBB in the SA group. A pooled estimate/meta-analysis was deemed fallacious in this case.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations